Isolated Limb Perfusion for the Treatment of Unresectable In-Transit Metastases of Cutaneous Squamous Cell Carcinoma - Barbosa,Joana (2021)
ABSTRACT Squamous cell carcinoma (SCC) is the second most common non-melanoma skin cancer and its incidence has been increasing over the past decades. SCC in-transit metastases are rare and predict a poor prognosis. We present the case of a 69-year-old patient with a right lower leg SCC, surgically excised with free margins. One month later, erythematous to violaceous, firm papules begin to erupt on the right lower leg, evolving to ulcerated nodules over a period of weeks. Homolateral inguinal and iliac nodal metastases were documented by percutaneous biopsy of an inguinal palpable lymph node and later documented by positron emission tomography - computed tomography (PET-CT). Given the unresectability of the disease, regional chemotherapy involving isolated limb perfusion (ILP) with melphalan and tumor necrosis factor-alpha (TNFα) was performed in order to avoid amputation. Macroscopic regression ensued, with complete resolution of all visible in-transit metastases 12 weeks after perfusion. However, a fatal outcome was observed 4 months later, due to systemic metastases. ILP is an effective and well-established technique in the treatment of advanced tumors of the extremities. Its main indications are in-transit metastases of malignant melanoma and advanced soft tissue sarcomas. However, studies have shown its effectiveness in other tumors such as locally advanced SCC. Despite the unfortunate outcome, it was possible to avoid amputation of the limb, with complete local disease remission.